2018
DOI: 10.1016/j.ijcha.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and mannose binding lectin in patients with rheumatoid arthritis from southern Brazil

Abstract: BackgroundMannose binding lectin (MBL) appears to be involved in susceptibility to rheumatoid arthritis (RA), in the inflammatory process and in the genesis of atherosclerotic disease.ObjectiveTo study the association of MBL serum levels and its genotypic variation with carotid arteries intimal thickness (IMT) in RA patients from Southern Brazil.MethodsMBL serum levels, MBL2 genotyping and IMT were investigated in 90 RA patients along with their demographic, clinical and laboratory profile. MBL levels and MBL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…116 Barbara et al found that RA patients had a significantly lower MBL serum concentration in relation to controls and found no statistically significant association between MBL and disease activity, ESR, autoantibodies, or IMT. 105 A cross-sectional study found that both high and low levels of MBL in RA patients were associated with an increased common carotid artery intima-media thickness (cc-IMT), indicating a quadratic U-shaped relation between serum MBL and ccIMT. 117 More studies would be valuable to assess whether MBL truly plays a role in mediating atherosclerosis in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…116 Barbara et al found that RA patients had a significantly lower MBL serum concentration in relation to controls and found no statistically significant association between MBL and disease activity, ESR, autoantibodies, or IMT. 105 A cross-sectional study found that both high and low levels of MBL in RA patients were associated with an increased common carotid artery intima-media thickness (cc-IMT), indicating a quadratic U-shaped relation between serum MBL and ccIMT. 117 More studies would be valuable to assess whether MBL truly plays a role in mediating atherosclerosis in RA patients.…”
Section: Discussionmentioning
confidence: 99%